An Integrated Agro-Livestock Model for Sustainable Intensification of Marginal Lands - Cori Qamara; Tri Hendarto; Yustinus C Sinaga; Revaldo Adhi Pramana; I Putu Gede Didik Widiarta (International Journal of Management, Accounting & Finance (KBIJMAF), 2025)
Degraded post-mining lands in East Kalimantan suffer from low soil fertility, reduced biodiversity, and limited economic value for local communities. Previous efforts, such as monoculture reforestation or single-sector agriculture, have produced limited ecological recovery and economic resilience. This study aims to develop a community-based sustainable business model and assess the ecological and economic impacts of an integrated cattle–forage–stingless bee system in post-mining regions. A mixed-methods approach combined qualitative techniques (in-depth interviews, focus group discussions) with quantitative analyses (carbon footprint, R/C ratio, B/C ratio) across five regencies, involving five key informants and thirty farmers. The system advances SDGs by increasing income through diversified products (SDGs 1, 2, 8), converting degraded land into carbon sinks (-12.05 tCO₂e/ha/year) (SDGs 13, 15), and supporting biodiversity through pollination (SDG 15). Its cyclical approach, aligned with SDG 12, transforms wastelands into sustainable agricultural landscapes, addressing climate and livelihood challenges. This is the first empirical study to link carbon sequestration and biodiversity gains with economic viability in a three-tier cattle–forage–stingless bee integration for post-mining landscapes.